Hubungan antara Aktivitas Fisik Harian dengan Kemampuan Motorik Kasar pada Anak di SDN 4 Pemecutan, Denpasar: Cross-Sectional Study - Komang Ayu Sanimita Ahrani; Made Hendra Satria Nugraha; Anak Agung Gede Eka Septian Utama; Ari Wibawa (Universitas Pahlawan Tuanku Tambusai, 2026)
Gross motor skills are an important aspect of development in elementary school children and are influenced by various factors, one of which is daily physical activity. This study aimed to determine the relationship between daily physical activity and gross motor skills in elementary school children at SDN 4 Pemecutan, Denpasar. This study employed an analytic observational design with a cross-sectional approach involving 58 children aged 8–10 years selected through purposive sampling. Daily physical activity was measured using the Physical Activity Questionnaire for Children (PAQ-C), while gross motor skills were assessed using the Test of Gross Motor Development-2 (TGMD-2). Data were analyzed using Spearman’s correlation test. The results showed a significant relationship between daily physical activity and gross motor skills (p < 0.001; r = 0.472), indicating a moderate positive correlation. It can be concluded that daily physical activity is associated with gross motor skills in elementary school children.